2010
DOI: 10.1111/j.1600-0447.2010.01625.x
|View full text |Cite
|
Sign up to set email alerts
|

Deep brain stimulation in the treatment of depression

Abstract: DBS is a promising treatment for therapy-refractory MDD. The published experience is, however, limited, and the method is at present an experimental therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 68 publications
0
30
0
Order By: Relevance
“…However, case observations are a valuable means of generating hypotheses and collecting information. This is especially relevant with regard to as yet experimental therapeutic methods such as DBS for the treatment of affective disorders, for which there is still limited clinical experience [23] and currently only one follow-up study [22] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, case observations are a valuable means of generating hypotheses and collecting information. This is especially relevant with regard to as yet experimental therapeutic methods such as DBS for the treatment of affective disorders, for which there is still limited clinical experience [23] and currently only one follow-up study [22] .…”
Section: Discussionmentioning
confidence: 99%
“…The recent adoption of deep brain stimulation (DBS) for psychiatric disease such as obsessive-compulsive disorder, Tourette's syndrome or major depression has already shown efficacy in a well-chosen, highly treatmentresistant collective [21][22][23] . While clinical results for patients suffering from chronic MDD are promising, the currently still experimental nature of DBS calls for a comprehensive analysis of mechanisms alongside the evaluation of antidepressant efficacy.…”
Section: Introductionmentioning
confidence: 99%
“…that has become the standard of care for movement disorders (1)(2)(3) and is under investigation in major depression (4)(5)(6). In DBS, chronic high-frequency stimulation of specific sites reduces symptoms in medically intractable illness.…”
Section: Eep Brain Stimulation (Dbs) Is a Neurosurgical Techniquementioning
confidence: 99%
“…Clinical trials have shown that DBS of the Acc may be an effective and safe treatment for refractory OCD and major depressive disorder and some case studies have shown positive effects of Acc DBS on alcohol and drug addiction and eating disorders [17,18,47,48,49,50,51,52]. …”
Section: Discussionmentioning
confidence: 99%
“…The Acc has recently become an important target for deep brain stimulation (DBS) in some of those disorders when refractory to best medical treatment [12,13,14,15,16,17,18]. DBS is a neurosurgical reversible technique that uses the chronic electrical stimulation of deep brain structures to block or modulate neuronal circuits.…”
Section: Introductionmentioning
confidence: 99%